Shaking table 2-D models of a concrete gravity dam. - Harris, David W.
One of the most famous and studied cases of dams subjected to earthquake loading is the Koyna Dam in India. In this study, a two dimensional model of Koyna Dam at 1/50 scale was used on a shake table to simulate effects and serve as data for non-linear computer model calibration. A new concrete mix was designed for the non-linear similitude modelling. This new mix provided the correct kinematic failure of concrete at scale. Two models were tested to failure : one with an initial shrinkage crack and one monolith. Reservoir effects were not modelled. The results of both models are discussed and compared. The ability to model non-linear effects is discussed.
Keywords: Concrete earthquake Koyna modelling dams